Precision Population Medicine in Primary Care: The Sanford Chip Experience - Christensen, Kurt D.; Bell, Megan; Zawatsky, Carrie L. B.; Galbraith, Lauren N.; Green, Robert C.; Hutchinson, Allison M.; Jamal, Leila; LeBlanc, Jessica L.; Leonhard, Jennifer R.; Moore, Michelle; Mullineaux, Lisa; Petry, Natasha; et al. (Frontiers in Genetics, 2021)
Genetic testing has the potential to revolutionize primary care, but few health systems have developed the infrastructure to support precision population medicine applications or attempted to evaluate its impact on patient and provider outcomes. In 2018, Sanford Health, the nation's largest rural nonprofit health care system, began offering genetic testing to its primary care patients. To date, more than 11,000 patients have participated in the Sanford Chip Program, over 90% of whom have been identified with at least one informative pharmacogenomic variant, and about 1.5% of whom have been identified with a medically actionable predisposition for disease. This manuscript describes the rationale for offering the Sanford Chip, the programs and infrastructure implemented to support it, and evolving plans for research to evaluate its real-world impact.